2018
DOI: 10.1007/s00284-018-1512-2
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Mechanism of Terpinen-4-ol Against Streptococcus agalactiae

Abstract: Streptococcus agalactiae, a highly contagious mastitis pathogen, caused huge economic losses; meanwhile, repeated use of antibiotics results in the emergence of serious antibiotic residues and drug resistance. Therefore, it is in great need to develop ecologically sustainable antimicrobial agents. In the study, the minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC), and action mechanism of terpinen-4-ol against S. agalactiae was investigated to evaluate antibacterial activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 26 publications
5
38
0
Order By: Relevance
“…The starting voltage was 60 V and the voltage of the sample changed to 120 V after entering the separating gel. After completing the electrophoresis, the gel was removed and then stained with Coomassie Brilliant Blue R-250, and the separated protein bands were obtained after decolorization [39].…”
Section: Leakage Of Proteinsmentioning
confidence: 99%
“…The starting voltage was 60 V and the voltage of the sample changed to 120 V after entering the separating gel. After completing the electrophoresis, the gel was removed and then stained with Coomassie Brilliant Blue R-250, and the separated protein bands were obtained after decolorization [39].…”
Section: Leakage Of Proteinsmentioning
confidence: 99%
“…A 20-µL volume of the bacterial suspension was then used to create slides, which were observed with a fluorescence microscope (LeicaDM1000, Leica). 46,47 UV Spectroscopic Test of the Interaction Between Luteolin and DNA Luteolin (final concentration, 1/2 MIC) was fully mixed with pBR322 DNA (1 µg/mL, TAKARA, Dalian, China) and incubated at 37 ºC for 30 min. The absorption spectrum, which ranged from 300 to 420 nm, was determined by an ultraviolet spectrophotometer (U-3900/3900H, Hitachi, Japan).…”
Section: Effect Of Luteolin On Nucleic Acidmentioning
confidence: 99%
“…The major compound, α-terpineol, from rhizomes of A. scabra and A. murdochii in this study has been reported by Li et al (2014) to exhibit strong antibacterial activity against Salmonella enteritidis and Staphylococcus aureus with MIC values of 1.56 and 3.13 µg/mL, respectively. Another study by Zhang et al (2018) showed that terpinen-4-ol exhibit anti-bacterial activity with MIC value of 98 µg/mL against Staphylococcus agalactiae. Terpinen-4-ol was present in leaf and rhizome oils of A. scabra and A. murdochii but in higher quantities in the latter.…”
Section: Anti-microbial Activitymentioning
confidence: 99%